ANALISA KADAR PROTEIN TELUR AYAM KAMPUNG (Gallus domesticus) TERHADAP LAMA PENYIMPANAN PADA SUHU 12 â 15 0C - Kunsah, Baterun (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
ANALISA KADAR PROTEIN TELUR AYAM KAMPUNGÂ  (Gallus domesticus)Â  TERHADAPÂ  LAMA PENYIMPANAN PADA SUHU 12 â 15 0CBaterun Kunsah, S.T., M.Si.Prodi D3 Analis Kesehatan UM SurabayaKunsah11980@gmail.comÂ AbstractProtein is a large molecule with a molecular weight of 5000 to tens of millions. Egg protein is one of high quality animal protein and easy to digest when compared with other types of animal protein, the protein is more abundant in egg yolk, which is as much as 16.5% egg yolk and egg white as much as 10.9%. Excess chicken egg is more complete, more savory and smelly lower levels. In the process of egg storage containers require eggs da RH and temperature shelf space that is conducive to maintaining the quality of chicken eggs. In particular the use of home stairs eggs stored in the refrigerator, cold storage is best done at the optimum temperature 12-15oC with 70-80% RH. At the pH of fresh egg yolk in one week 6.0 and 6.8 pH rises, the increase in pH with storage time of more than one week is cause dilution. Hence the need for the right information vulnerable long time storage and there is damage or not on Gallus domesticusÂ  chicken eggs to protein content to be stored at the optimum temperature.This research type is experimental, the sample of this study is the fresh henâs egg out of the village and its population is derived from Gallus domesticusÂ chicken egg farmers at Ngenep RT 2/RW1 Karang Ploso subdistrict of Malang. The method used for inspection of protein content is Kjeldhal Modified method it obtained the results of the protein levels at 0 days 12:37%, 13:09% 5 days, 10 days 13.74%, 14:24% 15 day, 20 day 15.83%, all of these results as the conclusion there is effect on the length of egg storage to the protein content on egg Gallus domesticus.Â Keyword : Protein analyze, Gallus domesticusÂ